Evaluation of Selected Large Patch-Tolerant Zoysia spp. for Performance in Kansas - Manoj Chhetri; Jack Fry; Megan Kennelly (Kansas Agricultural Experiment Station Research Reports, 2020)
Turf quality characteristics and large patch incidence of ten selected experimental zoysiagrass genotypes were evaluated during the 2018–2019 growing season in Manhattan, KS, and establishment rate of the same ten was evaluated in Olathe, KS. Although plots were inoculated withRhizoctonia solani(AG 2-2 LP) in September 2018 in Manhattan, no large patch occurred. However, the genotypes showed variability in turf performance measured by turf quality, spring greenup, fall color retention, and genetic color. In Olathe, KS, at Shadow Glen Golf Club, the ten genotypes were planted on June 17, 2019. The range in visual ground coverage on September 27, 2019, was 63.3 to 92.7%.
Keywords: Rhizoctonia; inoculation; transition zone